2009
DOI: 10.1016/j.expthermflusci.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Film thickness effects on calibrations of a narrowband thermochromic liquid crystal

Abstract: Thermochromic liquid crystals (TLCs) have been widely employed by researchers in heat transfer and fluid flow communities as a reliable and non-intrusive temperature measurement tool due to their unique optical properties such as birefringence, optical activity, circular dichroism and selective reflection of colours in the visible spectrum as function of temperature. The use of narrowband TLCs are attractive for temperature and heat transfer measurements due to their higher precision in temperature measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Rao and Zang [2], Camci et al [5], Farina et al [6], Behle et al [7], Sabatino et al [8], and Chan et al [9] studied experimentally the effects of the lighting angles and viewing angles on the hue-temperature calibration curves of the TLCs. Roth and Anderson [10], Wiberg and Lior [11], Abdullah et al [12], and Rao et al [13] studied experimentally the effects of the coating thickness on the TLC hue-temperature calibration curves. These previous researches only indicated that the lighting angle and the coating thickness can significantly affect the TLC hue-temperature calibration curves.…”
Section: Introductionmentioning
confidence: 99%
“…Rao and Zang [2], Camci et al [5], Farina et al [6], Behle et al [7], Sabatino et al [8], and Chan et al [9] studied experimentally the effects of the lighting angles and viewing angles on the hue-temperature calibration curves of the TLCs. Roth and Anderson [10], Wiberg and Lior [11], Abdullah et al [12], and Rao et al [13] studied experimentally the effects of the coating thickness on the TLC hue-temperature calibration curves. These previous researches only indicated that the lighting angle and the coating thickness can significantly affect the TLC hue-temperature calibration curves.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature was measured based on the observation of the thermochromic liquid crystal (TLC) color play on the target plate and fast response Ttype thermocouple data which gained from the data acquisition system. The TLC was calibrated first before been used in the experiment using the method stated by Abdullah et al [10]. The result acquired from the color changes of the TLC were captured by digital video camera.…”
Section: Methodsmentioning
confidence: 99%
“… Film thickness -Abdullah et al [7] found that the green intensity calibration curve for their narrowband TLC shifted by 0.4°C when increasing film thickness from 10μm to 50μm; they also observed an 18% increase in peak green intensity.  Ageing -Kakade et al [8] repeatedly heated narrowband TLC through their colour change limit.…”
Section: Thermochromic Liquid Crystals (Tlc)mentioning
confidence: 96%